Failure behavior of reinforced concrete slabs subjected to moderate-velocity impact by a steel projectile. Issue 3 (September 2017) - Kataoka, Shinnosuke; Beppu, Masuhiro; Ichino, Hiroyoshi; Mase, Tatsuya; Nakada, Tatsuya; Matsuzawa, Ryo
This study investigates the failure characteristics of reinforced concrete slabs subjected to moderate-velocity impacts by conducting impact tests and numerical simulations. In a series of tests, a spherical steel projectile with a mass of 8.3 kg and a diameter of 80 mm is collided with an reinforced concrete slab at an impact velocity of 65–90 m/s. To investigate the failure characteristics of the reinforced concrete slab, impact motion of the projectile, reaction force, and strain–time history on the back surface and reinforcing bars of the reinforced concrete slab were measured. Failure modes obtained experimentally were compared with the Central Research Institute of Electric Power Industry formula proposed for the local damage of reinforced concrete slabs. Test results revealed that a circular scabbing crack on the back surface of the reinforced concrete slab was completed while there is a sharp increase in the reaction force. Numerical simulations using a high-fidelity concrete model reasonably reproduced the failure characteristics of an reinforced concrete slab. Numerical results demonstrated that the scabbing failure of an reinforced concrete slab subjected to a moderate-velocity impact was initiated by the penetration of the projectile and was completed during the reaction force response.